The Effect of Problem Prompting Learning Model Assisted by Mentimeter Media on Critical Thinking Ability Students - Andi Badli Rompegading; Muhammad Basriadi; Muhammad Nasir; Surya Satar (Postgraduate, University of Mataram, 2023)
The purpose of this study is to ascertain the impact of the Probing Prompting learning model supported by Mentimeter media on the critical thinking abilities of class X MIPA SMA Negeri 2 Soppeng students. The study was carried out at SMA Negeri 2 Soppeng. This study was conducted in April. A control group design with a pre-test, post-test, and quasi-experimental design is used in this study. The population of this study consisted of all students in class X MIPA SMA Negeri 2 Soppeng; the sample was taken from classes X MIPA 1 and 3, each of which had 25 students; class X MIPA 1 served as the experimental class, and class X MIPA 3 served as the control class. The research tool utilized in this study was a description test with 10 numbers. Based on data analysis, it was possible to determine how well students were able to use critical thinking when reading about environmental contamination. The results of the hypothesis test (t-test) demonstrate that for the post-test of both classes, tcount>ttable equals 11.66>1.67. When the results of the hypothesis test for the Pre-test value in both classes reveal tcount ttable, which is -2.13 1.67, then H0 is accepted and H1 is rejected. This is in compliance with the criteria in the hypothesis test